Comparative assessment of geometric stability in plastic zone of arteriotomy with сarotid artery endarterectomy - K. M. Vakhitov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2016)
Carotid artery endarterectomy (KEAE) is a worldwide standard operation in revascularization of brain. KEAE methodology is wellknown, proven and used in many health care facilities.The aim of our examination was: 1) to study anatomic changes of plastic zone of arteriotomic opening when making plastic repair of the latter with autovein patch; 2) to estimate geometric stability of plastic zone of arteriotomy of autovein patch with eversion technique carotid endarterectomy. According to received data, patients with classic carotid endarterectomy, using the autovein patch, has a predisposition to aneurysmatical transformation of plastic zone, with forming of maximal extension in the zone of bifurcation of CCA. Herewith, blood flow in the zone of maximal extension became turbulent with significant speed losses. In group with the eversion carotid endarterectomy, zone dilatation was not detected, despite all factors which trigger forming of dilatation of plastic zone among patients with autovein plastic repair.